Organizational Factors Affecting Law Enforcement Loyalty: An Islamic Leadership Perspective Using SEM-PLS Approach - Rowiyani; Khoerul Soleh; Latifah; Cahyani Tunggal Sari; Muhammad Haikal Darmawan (International Journal of Islamic Business and Economics (IJIBEC), 2025)
This study aims to analyze the influence of organizational factors—workload, institutional policy support, leadership, competency and training, and incentives—on human resource loyalty within law enforcement institutions, viewed through an Islamic leadership perspective. Employing a quantitative approach with a survey design, data were collected from 100 law enforcement officers involved in narcotics prevention and eradication efforts in Semarang City, Indonesia. The data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The results reveal that leadership has the strongest and most significant effect on human resource loyalty, followed by incentives and institutional policy support, while competency and training, and workload show weaker effects. The model demonstrates a very high explanatory power, with an R² value of 0.975, indicating that organizational factors collectively account for 97.5% of the variance in human resource loyalty. The findings highlight that leadership characterized by amanah (trustworthiness), adl (justice), and ihsan (excellence) is the cornerstone of employee commitment and institutional harmony. Fair incentives and consistent policy support further enhance loyalty through organizational justice and collective welfare (maslahah). This study contributes to the enrichment of Islamic Human Resource Management (IHRM) literature by integrating ethical and spiritual dimensions into the understanding of loyalty. Practically, it emphasizes that leadership grounded in Islamic ethics, supported by fair institutional structures, fosters not only professional dedication but also barakah (divine blessing) and sustainable organizational integrity.